Headmasters practice of transformational leadership, Malaysia - Salleh, Mohamad Johdi; Saidova, Parvina (LAP LAMBERT Academic Publishing, 2013)
The book discusses a study on the headmasters’ perception of practicing of effective transformational leadership in Malaysia. The samples are 176 headmasters of selected primary schools, comprises of 114 (64.8%) male and 62 (35.2%) female. The study found that majority of headmasters rated themselves as transformational leaders on an average level. Pearson Correlation (r) results showed significant correlation of practice and effectiveness of four dimensions of transformational leadership perceived by headmasters. This probably indicates that the respondents who practiced transformational leadership they perceived it as effective. The result of the T-test analysis showed that there was a significant difference between male and female headmasters in practicing transformational leadership. The female headmasters seemed to exhibit more transformational behaviors as compare to male headmasters. Therefore, the findings of this study suggest that the women are more transformational leaders than the men regardless of any type of organizations, school or non school settings.